DDT and HCH Residues in Muscle and Organs of Buffaloes - Muthukumar, M.; Reddey, K. Sudhakar; Reddy, K. Kondal; Reddy, A. Gopala; Reddy, D. Jagdishwar; Reddy, C. Narendra; Kondaiah, N. (Journal of Meat Science, 2011)
Organochlorines (OC) pesticides viz., DDT (Dichloro Diphenyl trichloroethane) and HCH (Hexachloro Cyclo Hexane) residues in muscle and organs of buffaloes collected from Hyderabad city were estimated by gas chromatograph. Majority of the analysed muscle and organs samples of buffaloes contained residues of metabolites of DDT - p,pDDT (para para Dichloro Diphenyl Trichlore ethane), p,pDDD (para para Dichloro Diphenyl Dichloroethylene) and p,pDDE (para para Dichlorodiphenyl Dichlore Ethane) and isomers of HCH (á , â, ã and ä HCH) pesticides. However, the levels of contamination in all the analysed tissue were below the maximum residue limit. Among the residues, the concentration of ä HCH (0.263 ppm) was more followed by p,pDDT (0.156 ppm), p,pDDE (0.114 ppm), â HCH (0.111 ppm), p,pDDD (0.084 ppm), á HCH (0.061 ppm) and ã HCH (0.057 ppm). The highest concentration p,pDDD and â HCH were found in muscle, whereas the level of p,p 4-DDT, á HCH, ã HCH and ä HCH were highest in liver. The kidneys showed more amount of p,pDDE.